Exploring the mechanism of fraxetin against acute myeloid leukemia through cell experiments and network pharmacology - Tingting Fang; Lanqin Liu; Wenjun Liu (BMC, 2024)
Abstract Objective Previous studies have shown that fraxetin has antitumor activity in a variety of tumors, but its role in acute myeloid leukemia (AML) remains unclear. In this study, we aimed to evaluate the anti-AML effect of fraxetin through cell experiments and network pharmacology analysis. Methods The inhibitory and apoptotic effects of fraxetin on AML cells were determined by CCK-8 and flow cytometry experiments. Potential targets of fraxetin and AML-related targets were screened using public databases. PPI network, GO functional enrichment and KEGG pathway enrichment analyses were performed to predict the hub targets and signaling pathways by which fraxetin alleviates AML. Molecular docking was used to determine the fraxetin binding sites on hub targets. Using the GEPIA database, the expression of hub targets was analyzed in relation to the overall survival of AML patients. Results Cell experiments showed that fraxetin inhibits AML cell proliferation and induces apoptosis. To explore the potential mechanism of fraxetin, 29 shared targets of fraxetin and AML were obtained through screening online public databases. Among them, AKT1, TNF, SRC, etc., are related to AML cell apoptosis. The expression levels of SRC, NOS3, VAV1, LYN, and PTGS1 were associated with the overall survival of AML patients (p value < 0.05). The enrichment analysis results identified the main pathways, namely, focal adhesion and the PI3K-AKT signaling pathway, that affected the proliferation and apoptosis of AML cells. The analysis of hub targets of the PPI network showed that AKT1, TNF, CTNNB1, etc., were hub targets, which were related to the proliferation and apoptosis of AML cells. The results of molecular docking showed that the hub targets had good binding with fraxetin. Conclusion Fraxetin may inhibit AML cell proliferation and induce AML cell apoptosis through multiple targets, such as AKT1, SRC, and EGFR, and multiple pathways, such as focal adhesion and the PI3K-AKT signaling pathway.